Juridical Overview of the Position of the Regional Representative Council (DPD) of the Republic of Indonesia in the Legislation System in Indonesia - David Aprizon Putra (NEGREI: Academic Journal of Law and Governance, 2022)
The establishment of the Regional Representative Council (DPD) is also intended to reform the structure of representation in Indonesia into two chambers (bicameral), so that the People’s Consultative Assembly (MPR) consists of the DPR and DPD. With this bicameral structure, it is hoped that the legislative process can be carried out based on a double-check system that allows the representation of the interests of all the people to be relatively distributed on a broad social basis. This research is a normative juridical research, trying to explore and analyze problems using a conceptual approach and legislation.  It is strongly felt that the functions and powers as stated in Article 22 D of the 1945 Constitution after the amendments are difficult to realize the aims and objectives of the establishment of the DPD RI, especially with the provisions in the MD3 Law and the PPP Law. However, now after the issuance of the Constitutional Court of Indonesia’s decision stating that the provisions in the MD3 Law and the PPP Law related to the DPD's authority were declared contrary to the Constitution, now the DPD has an equal position and has equal rights and obligations with the DPR and the President in terms of formulating legislation. With this equal position, the DPD can submit a Draft Law (RUU) related to the region, which includes autonomy, financial balance between the center and the regions, the relationship between the central and regional governments, the formation and expansion and amalgamation of regions, as well as natural resource management. It is hoped that after the decision of the Constitutional Court, the performance of the DPD, especially in the service of forming regulations related to autonomy and development. After the decision of the Constitutional Court, the performance of the DPD, especially in the service of forming regulations related to autonomy and development, is expected